Romania’s Food System Vulnerability: Peste des Petits Ruminants Effects on the Agri-Food Sector - Petre Adrian Liptac; Mihaela Pila; Silvius Stanciu (Journal of Agriculture and Rural Development Studies, 2025)
In Romania, the consumption of lamb/kid meat is mainly associated with the Easter holidays, as Romanians are not among the top consumers at the European level. This paper proposes an analysis of the sheep/goat meat market in Romania in the context of the Peste des Petits Ruminants (PPR) outbreak. The bibliographic documentation considered open-access articles from major scientific databases, complemented by reports from public institutions. The research used data from European and national statistics concerning the epidemic’s manifestation, price trends, and sheep meat consumption in Romania. The study highlighted the virulent spread of the PPR epidemic, which had a significant impact on sheep and goat farms. The ban on live animal exports at the European level, combined with the lack of appropriate sheep/goat meat processing units, has substantially affected the domestic sector. Although traditional contracts exist with non-EU partners, live animal exports now incur additional food safety costs. The increased supply of sheep/goat meat on the domestic market will likely ensure a relative price stability for lamb/kid meat during the 2025 Easter season. However, in the long term, the competitiveness of the small ruminant farming sector in Romania will be negatively impacted. The study contributes to the understanding the Romanian agri-food market vulnerabilities and may serve as a basis for public policy interventions and market forecasting tools in the context of animal health crises.